A Discourse Analysis of Plantation Commodity Processing Advertisements in East Sumatran Newspapers (1870-1930) - Syahri Ramadhan; Melly Tria Utari (Yupa: Historical Studies Journal, 2026)
This research aims to analyze the background behind the emergence of advertisements related to the processing of plantation commodities in newspapers, using Van Dijk's theoretical approach. The data sources for this study are the newspapers Pewarta Deli, Suara Dairi, and Surya Sibolga. The method used in this research is the historical method, which is examined through four stages, heuristics (source collection), data verification (validating sources), interpretation (analysis); and historiography. Data analysis is conducted using Van Dijk’s theory. The results of this research indicate that there is a connection between the advertisements for processed plantation commodities in the newspapers Pewarta Deli, Suara Dairi, and Surya Sibolga, and the implementation of the 1870 Agrarian Law by the Dutch East Indies government. These newspapers served as a platform to market or sell the abundant outputs of the plantation industry, which significantly increased due to the application of the 1870 Agrarian Law.